Analisis Penerapan Audit Manajemen dalam Fungsi Keuangan untuk Mengukur Efektivitas dan Efisiensi Manajemen Keuangan Kebun Berangir PT Perkebunan Nusantara IV Labuhanbatu Utara - Sri Rahayu; Kusmilawaty; Laylan Syafina (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to analyze the application of audit management in the financial function to measure the efectiveness and eficiency of financial management at berangir plantation PT Perkebunan Nusantara IV Labuhanbatu Utara. Management audit is an important tool for assessing performance and eficiency in financial management of a plantation company. By utilizing relevant financial data, this research identifies the factors that influence the efectiveness and eficiency of financial management in Berangir Gardens. The research method used is descriptive qualitative with a case study approach. The necessary data were collected through interviews, observation and analysis of documents from PT Perkebunan Nusantara IV Labuhanbatu Utara Berangir Plantation. Furthermore, the data is analyzed using content analysis techniques to identify findings and patterns related to the implementation of audit management and financial performance. The results of the study show that the implementation of audit management in the financial function plays an important role in measuring the efectiveness and eficiency of financial management at Kebun Berangir. These findings can provide insight for company management to improve financial performance and resource management. In addition, this study also provides recommendations regarding corrective measure that can be implemented to increase the eficiency and efectiveness of financial management in these plantation companies.